Le « rôle homosexuel » trente ans plus tard : retour sur le travail de Mary McIntosh - Jeffrey Weeks (Genre, Sexualité et Société)
There is a tendency to efface the theoretical origins of social constructionist approaches to sexuality, with an accompanying tendency to privilege the contribution of Michel Foucault and his followers. Without in any way minimizing Foucault’s significance, it is important to recover the earlier attempts to theorize the social and cultural shaping of sexuality in general and homosexuality in particular. In this context Mary McIntosh’s article ‘The Homosexual Role’, published 30 years ago, stands out with founding significance. After outlining the central argument of McIntosh’s essay, this paper suggests that it is best understood in terms of three key oppositions: between homosexual behaviour and homosexual category; between the pre-modern and the modern; and between heterosexuality and homosexuality. Within this framework, McIntosh’s essay can be seen as a crucial moment in the shaping of social constructionism. It is also a key text in McIntosh’s own influential body of work, which has consistently attempted to denaturalize the social.